2011
DOI: 10.1155/2011/528425
|View full text |Cite
|
Sign up to set email alerts
|

Single-Switch User Interface for Robot Arm to Help Disabled People Using RT-Middleware

Abstract: We are developing a manipulator system in order to support disabled people with less muscle strength such as muscular dystrophy patients. Such a manipulator should have an easy user interface for the users to control it. But the supporting manipulator for disabled people cannot make large industry, so we should offer inexpensive manufacturing way. These type products are called "orphan products." We report on the construction of the user interface system using RT-Middleware which is an open software platform f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Before beginning the human ergonomics experiments, we confirmed that RAPUDA could handle all of the objects in the above list under experimental conditions. RAPUDA has a single switch and an auto scan panel as its user interface [14]. With this interface, people with muscle dystrophy can easily control RAPUDA ( Figure 10).…”
Section: B Participants In Rapuda Human Ergonomics Experimentsmentioning
confidence: 99%
“…Before beginning the human ergonomics experiments, we confirmed that RAPUDA could handle all of the objects in the above list under experimental conditions. RAPUDA has a single switch and an auto scan panel as its user interface [14]. With this interface, people with muscle dystrophy can easily control RAPUDA ( Figure 10).…”
Section: B Participants In Rapuda Human Ergonomics Experimentsmentioning
confidence: 99%
“…Upper-limb disAbilities) is a novel robotic arm with linear mechanism developed at AIST. By utilizing the RAPUDA, we have demonstrated that a bottle of water can be picked up from a table and taken to the mouth using a simple joystick or single-switch interfaces [23]. However, the representation of the specification such as "RAPUDA is capable of bringing a bottle of water from a table to a mouth.…”
Section: Evaluation Of Assistive Robotsmentioning
confidence: 99%
“…Many assistive technologies have been developed to assist people with DASH to interact with the environment. The related studies supporting DASH have focused on the automation of objects for their mobility [1]. These include replacement technologies such as an exoskeleton, robotic arms or a prosthetic arm are among the common solutions for assisting people with DASH [2].…”
Section: Introductionmentioning
confidence: 99%